Programmed cell death 4 (PDCD4) expression during multistep Barrett's carcinogenesis. Issue 8 (11th August 2010) - Fassan, Matteo; Pizzi, Marco; Battaglia, Giorgio; Giacomelli, Luciano; Parente, Paola; Bocus, Paolo; Ancona, Ermanno; Rugge, Massimo
Abstract : Aim: To test the contribution of programmed cell death 4 ( PDCD4 ) tumour suppressor gene in Barrett's carcinogenesis. Methods: PDCD4 immunohistochemical expression was assessed in 88 biopsy samples obtained from histologically proven long-segment Barrett's mucosa (BM; 25 non-intestinal columnar metaplasia, 25 intestinal metaplasia (IM), 16 low-grade intraepithelial neoplasia (LG-IEN), 12 high-grade IEN (HG-IEN) and 10 Barrett's adenocarcinoma (BAc)). As controls, 25 additional samples of native oesophageal mucosa (N) were obtained from patients with dyspepsia. To further support the data, the expression levels of miR-21, an important PDCD4 expression regulator, in 14 N, 5 HG-IEN and 11 BAc samples were determined by quantitative real-time PCR analysis. Results: PDCD4 immunostaining decreased progressively and significantly with the progression of the phenotypic changes occurring during Barrett's carcinogenesis (p<0.001). Normal basal squamous epithelial layers featured strong PDCD4 nuclear immunoreaction (mostly coexisting with weak–moderate cytoplasmic staining). Non-intestinal columnar metaplasia and intestinal metaplasia preserved a strong nuclear immunostaining; conversely, a significant decrease in PDCD4 nuclear expression was seen in dysplastic (LG-IEN and HG-IEN) and neoplastic lesions. Weak–moderate cytoplasmic immunostaining was evident in cases of LG-IEN, while HG-IEN and BAc samples showed weak cytoplasmic or no protein expression. As expected, miR-21 expression was significantly upregulated in HG-IEN and BAc samples, consistently with PDCD4 dysregulation. Conclusions: These data support a significant role for PDCD4 downregulation in the progression of BM to BAc, and confirm miR-21 as a negative regulator of PDCD4 in vivo. Further efforts are needed to validate PDCD4 as a potential prognostic marker in patients with Barrett's oesophagus.